2010
DOI: 10.4314/ijbcs.v3i6.53169
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation of maize (<i>Zea mays</i>) cob by <i>Pleurotus ostreatus</i> strain EM-1: Biopolymer profiles and cellulose degradability

Abstract: The low digestibility and low protein content of maize cob are major limitations to its use as animal feed in Ghana. The possibility of enhancing the feed potential of maize cob through solid state fermentation by Pleurotus ostreatus strain EM-1 was investigated. At the end of spawn run, lignin, cellulose and hemicellulose content had decreased by 42.3, 5.6% and 41.0% respectively. No further reduction in lignin content occurred thereafter. In contrast, after 28 days, cellulose and hemicellulose had been degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The higher reducing sugar released from groundnut shell degraded by the monoculture of Pleurotus ostreatus and Lentinus squarrosulus than co-culture of the two might be due to the high utilization of the released reducing sugar as carbon and energy sources by the co-culture than monoculture [30,31] or the organisms might be having an antagonistic effect on each other leading to decrease in released reducing sugar when grown together. While the observed higher reducing sugar released in Pleurotus ostreatus and Lentinus squarrosulus-degraded maize cob than non-degraded one was probably because of the interaction between hydrolytic and oxidative enzymes released by these organisms when degrading maize cob, breaking down cellulose and hemicellulose to simple sugar [32,33]. A similar observation of increased reducing sugar content of maize cob, when degraded by Pleurotus ostreatus, was reported by Adamafio, et al [32].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The higher reducing sugar released from groundnut shell degraded by the monoculture of Pleurotus ostreatus and Lentinus squarrosulus than co-culture of the two might be due to the high utilization of the released reducing sugar as carbon and energy sources by the co-culture than monoculture [30,31] or the organisms might be having an antagonistic effect on each other leading to decrease in released reducing sugar when grown together. While the observed higher reducing sugar released in Pleurotus ostreatus and Lentinus squarrosulus-degraded maize cob than non-degraded one was probably because of the interaction between hydrolytic and oxidative enzymes released by these organisms when degrading maize cob, breaking down cellulose and hemicellulose to simple sugar [32,33]. A similar observation of increased reducing sugar content of maize cob, when degraded by Pleurotus ostreatus, was reported by Adamafio, et al [32].…”
Section: Discussionsupporting
confidence: 80%
“…While the observed higher reducing sugar released in Pleurotus ostreatus and Lentinus squarrosulus-degraded maize cob than non-degraded one was probably because of the interaction between hydrolytic and oxidative enzymes released by these organisms when degrading maize cob, breaking down cellulose and hemicellulose to simple sugar [32,33]. A similar observation of increased reducing sugar content of maize cob, when degraded by Pleurotus ostreatus, was reported by Adamafio, et al [32]. The increase in reducing sugar content observed in degraded maize straw could © 2023 Conscientia Beam.…”
Section: Discussionmentioning
confidence: 83%
“…Adamafio et al also found that cellulose was double after fermenting corn cob with P. ostreatus. Solid state fermentation with P. ostreatus decrease accumulated fiber by enzymes activities 13 . It is indicated that mushroom contains several enzymes that involves lignocellulose metabolism 14 .…”
Section: Reduced Sugarmentioning
confidence: 99%
“…The utilization of lignocellulose wastes for cellulose production increases interest worldwide and in sub-saharan countries in particular. That is how the degradability of cellulose in maize cob used for animals feed in Ghana was investigated by Adamafio et al (2009), and the capability of pumpkin cellulose to remove heavy metals was recently studied in Nigeria (Eze et al, 2013). The trend of Abelmuscus esculentus powder to have good swelling and hydration aptitude displayed its strong potential as pharmaceutical raw material in tablet formulation (Bakre and Jaiyeoba, 2009).…”
Section: Introductionmentioning
confidence: 99%